2019
DOI: 10.1007/s40475-019-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Current Gaps and Needs for Increasing Access to Healthcare for People with Chagas Disease in the USA

Abstract: Purpose of Review In the USA, fewer than 1% of people with Chagas disease (CD) are diagnosed and treated. Patients and physicians confront significant barriers to initiating testing and treatment, which are not systematically available in the US health care system. What are these barriers and how can they be overcome? We discuss the broader challenges and state-level dynamics of CD in several of the US states with the highest burdened populations. Recent Findings The principal challenges for expanding access t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 61 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…(5, 9, 10) Although Chagas disease is most commonly found in Latin American countries, there has been a growing concern that it is vastly underestimated in the United States (1-5, 9, 11) Estimates that use modeled data suggest that there are between 326,000 and 347,000 individuals born in Latin America living in the United States that are infected with T.cruzi. (2,3,12) This population may hold the highest burden of Chagas disease in the United States due to a higher prevalence in their countries of origin. (13,14) However, in the southern United States there have been an increasing number of autochthonous and congenital transmission cases being reported since 2000.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…(5, 9, 10) Although Chagas disease is most commonly found in Latin American countries, there has been a growing concern that it is vastly underestimated in the United States (1-5, 9, 11) Estimates that use modeled data suggest that there are between 326,000 and 347,000 individuals born in Latin America living in the United States that are infected with T.cruzi. (2,3,12) This population may hold the highest burden of Chagas disease in the United States due to a higher prevalence in their countries of origin. (13,14) However, in the southern United States there have been an increasing number of autochthonous and congenital transmission cases being reported since 2000.…”
Section: Introductionmentioning
confidence: 99%
“…(18,27) Regardless of where a person is infected, less than 1% of people in the United States will ever receive a clinical diagnosis of Chagas disease and even fewer will ever receive treatment. (4,12) This lack of diagnosis and treatment is a result of a combination of factors including an absence of awareness by healthcare providers, limited diagnostic tools, and access to healthcare by the populations most vulnerable to this disease. (12,28,29) According to Lynn, et al, they found that shared risk factors for transmission of Chagas disease in the United States were living in a rural area and/or a history of outdoor activities or work.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations